Protein C Deficiency – Response to Danazol and DDAVP - Gonzalez, R; Alberca, I; Sala, N; Vicente, V (Thrombosis and Haemostasis, 1985)
We studied a Spanish family in which one of the female members presented recurrent thrombophlebitis in both legs after three different deliveries. Biological and antigenic activity of protein C was decreased (35% and 42% respectively). Reduced protein C levels were also observed in 6 other family members. Administration of danazol (600 mg/day) in two patients with protein C deficiency elevated this protein and discontinuation of the drug resulted in a reduction of protein C to pretreatment values. The proposita showed a normal fibrinolytic activity and infusion of DDAVP produced a similar response of FVIII/VWF and plasminogen activator to those observed in healthy subjects.
Keywords: Protein C deficiency; Recurrent thrombosis; Danazol; DDAVP